Odpowiedzi

2010-03-25T15:24:25+01:00
A)
A = ( 4; b), B = ( -a ; -a)
W symetrii osiowej względem osi OX mamy:
x' = x
y' = - y zatem
-a = 4 --> a = -4
-a = - b ---> b = a = -4
a = b = - 4
Odp. A = (4; -4) oraz B = (4 ; 4 )
b)
A = (2 ; b -4) , B =(-2a -4; 5)
zatem
-2a - 4 = 2 --> -2a = 2 +4 = 6 --> a = 6:(-2) = -3
5 = -(b - 4) = -b + 4 --> b = -1
a = -3 oraz b = -1
Odp.
A =( 2; -5) , B = ( 2; 5)
c)
A = (-b +5; 2a - 1), B = (-2a - 4 ; -a +2)
zatem
-2a - 4 = -b + 5 oraz -a +2 = -(2a - 1)
czyli -a +2a = 1 -2 oraz b = 2a + 4 +5
a = -1 oraz b = 2*(-1) + 9 = -2 +9 = 7
a = - 1 oraz b = 7
Odp.
A =(-2; -3 ) , B = ( -2 ; 3)
10 4 10